Development of Primary Cell Lines from Gill, Kidney, Spleen and Caudal Fin of Common Carp (Cyprinus carpio) - Insariani Insariani; Trisniaty Trisniaty; Freddy Riatmono; Abdul Ghani (Jurnal Ilmiah Perikanan dan Kelautan, 2020)
Highlihgt • Develop primary cultures derived From  tissue tails fins, gills, kidney and spleen from local Indonesian carp (Cyprinus carpio). • Primary culture cell with L15  Media • cell cultures  consist of two type Fibroblast-like and epithelial –like cell Abstract The fish cell lines technology have been developed for the interests of the fisheries world. This study aimed at developing a primary cell line from gill, kidney, spleen, and caudal fin of a common carp (Cyprinus carpio). A healthy common carp weighing 20 g (~1 month) was collected from the Cijeruk Fish Seed Center, Bogor. The development of primary cell lines from the gill, fin, tail, kidney and spleen tissue was performed in cell culture medium Leibovitz’s L-15 supplemented with 20% serum fetal bovine, 250 IU Penicillin, 250 µg / ml kanamycin sulfate and 2Mm L-Glutamine, and incubated at 28°C. Primary cell lines of caudal fin and gill began to form a monolayer on day 17 after culture. While the development of cell lines from kidney and spleen, although the initiation of cells and cells spread on the surface into a monolayer, was not perfect; therefore, the passage was unable to be done. Microscopic observations and Giemsa staining showed primary cell lines of caudal fin and gill based on cell morphology consisted of two cell types, fibroblast-like cells and epithelial-like cells. The first passage was done on day 17 when the confluence was more than 50%. The next passage was carried out every 3 weeks when confluence reached 70% -80%. The primary cell culture of gill was successfully passaged as much as 72 and the caudal fin was successfully passed as much as 89 times over 7 years. These new cell lines can be further used to propagate fish viruses and other biotechnology assays.